Flexible electromagnetic radiation shields based on carbon-containing glued compounds - E. S. Belousova; A. M. Mohamed; M. S. Al-Mahdawi; A. M. Prudnik (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The research results of obtaining process of flexible electromagnetic radiation shields with particles incorporation in fiber or foam base by impregnating carbon-containing glued compounds are given. Micrographs of surfaces and cross sections of the samples which show the distribution of carbon particles in the material are shown. Frequency characteristics of reflection and transmission coefficients of such carbonaceous materials are analyzed.